Harmonising corporate taxes in Europe - Devereux, M; Pearson, M (1990)
Although it is now over twenty years since the European Commission first published proposals concerning the harmonisation of corporate taxes, the debate on the desirablility of any such reform has not yet achieved a high political profile. However, it seems likely that the elimination or reduction of many other obstacles to business within Europe as part of the 1992 'Single Market' programme may lead to a greater awareness of the costs of the maintaining twelve different corporate tax systems within the Community.